Assessment of possible human risk of probiotic application in shrimp farming - Shakibazadeh, Shahram; Saad, Che Roos; Christianus, Annie; Kamarudin, Mohd Salleh; Sijam, Kamaruzaman; Sinaian, P. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Aquaculture is one of the fastest growing industries. This impressive industry is incorporated with prophylactic use of antibiotic for disease prevention. Probiotics seems to be appropriate substitute for the antibiotic, but because those are live bacteria and residual of the probiotics in the aquaculture product may cause health problem for the consumers and labors in the aquaculture processing plant and aquaculture farms. In this study we used LD50 in a mammalian model animal to assess the safety of probiotics used in shrimp culture for human consumption. After assessment for an approximate range of lethality in a preliminary experiment, treatment groups were fed via a gavage with certain dosage range of candidate probiotic, Shewanella algae. The LD50 value was approximately 1036 cfu/animal with 95% fiducial limitation of 34.95 (lower band) and 37.07 (upper band), which is fairly high and most likely safe to use as probiotic. Furthermore, this study may aid to onset of thinking about an evaluation technique for safe using of probiotic in aquaculture.